FAKTOR YANG MENDUKUNG PELAYANAN PEMBUATAN SURAT IZIN MENGEMUDI (SIM) DIWILAYAH KEPOLISIAN RESORT KOTA BESAR (POLRESTABES) SURABAYA - Herlina, Herlina (Universitas 17 Agustus 1945 Surabaya, 2017)
FACTORS SUPPORTING SERVICES MAKING DRIVING LICENSES (SIM) IN POLICE REGION OF BIG CITY (POLRESTABES) SURABAYA. The authority to grant a motor vehicle license in Indonesia is legally owned by the Police of the Republic of Indonesia (Polri). However, as one of the agencies authorized in the service of making a Driver's License (SIM), there is often a problem in the bhayangkara corps alias the police. In addition to the problem brokering Public complaints related to the creation of Driver's License (SIM) is the service of making Driver's License (SIM) executed by police officers not in accordance with the wishes of the community, Therefore, the need for adequate and qualified human resources can create more efficient and more cooperative public services. The focus in this research is the factors that support the service of making Driver's License (SIM) in the Police Town Resort Police area (Polrestabes) Surabaya. The method used in this research is qualitative descriptive type. The results of this study are factors that support the performance of bureaucracy that can be seen from the indicators of the ability of officers, quality of human resources, government support, and working conditions in providing excellent service quality and professional. Suggestions in this study is to be more maintained and improved again in providing public services, especially in the service of making this driver's license (SIM).Â Â Keywords: public service, human resource performance.